Analysis of the structural framework for schools affected by the Sunda Strait Tsunami in Pandeglang Regency - Bohari, Jazmi Adlan; Widana, I Dewa Ketut Kerta; Bahar, Fauzi; Widyaningrum, Nrangwesthi (Technium Social Sciences Journal, 2021)
The Sunda Strait tsunami disaster in 2018 claimed the lives of more than 430 people and caused various damage to infrastructure in coastal areas. This disaster also had an impact on the education sector. Schools located in disaster-prone areas are vulnerable to building damage that causes casualties and psychological problems for students. The west coast of Pandeglang Regency is a tsunami-prone area and is home to hundreds of elementary and high school schools in the area. The aim of this study is to analyze of the structural framework for schools affected by the sunda strait tsunami. The research locus was determined by purposive sampling in three locations: MTs Masyariqul Anwar in Labuan, SDN Mekarjaya 3 in Panimbang, and SDN Tamanjaya 2 in Sumur. This research data analysis uses qualitative data analysis techniques by Miles, Huberman and Saldana (2014). This research used disaster school survey form issued by National Disaster Management Agency (BNPB) which regulated in Head of BNPB Regulation No. 4 of 2012 on Implementation Guidelines of Disaster Safe Schools. The research finding that MTs Masyariqul Anwar, SDN Mekarjaya 3, and SDN Tamanjaya 2 can be concluded that MTs Masyariqul Anwar and SDN Tamanjaya 2 have a good level of school security with some notes that need to be improved. Meanwhile, SDN Mekarjaya 3 has a sufficient level of school security with several factors that are so inadequate that they must be repaired and improved immediately.